24 Spinal analgesia in patients undergoing transapical aortic valve implantation: improved outcomes in a routine cohort. (24th April 2016) - Silaschi, M; Alcock, E; Aldalati, O; Keshavarzi, F; Rajagopal, K; MacCarthy, P; Dworakowski, R; Wendler, O
Abstract : Introduction: Epidural analgesia improves outcomes after transapical aortic valve implantation (TA-AVI). However, it is rarely used due to the risk of complications in patients on antiplatelet or anticoagulant medication. Spinal analgesia (SA) is associated with fewer complications. We used SA in patients undergoing TA-AVI and report on outcomes. Methods: All TA-AVI patients received general anaesthesia. Since 2013, additional single-shot SA using a long acting opioid plus local anaesthetic intrathecally was used (n = 26). We compared results to a control group of patients without SA (n = 110). Results: Mean age was 79.3 ± 8.8yrs (SA) vs. 82.6 ± 7.1yrs (non-SA, p = 0.04). No SA related complication occurred. Up to 30-days, no patient died in the SA cohort compared to 18 deaths in the non-SA group (16.4%, p = 0.02). Increase in creatinine was lower in the SA group (18.5 ± 36.3mmol/l vs. 53.2 ± 74.7mmol/l, p = 0.02). After SA, no patient required dialysis vs. 10.0% (p = 0.12). No patient had respiratory failure in the SA group vs. 12.7% in non-SA (p = 0.05). New onset of atrial fibrillation occurred in 3.8% in SA vs. 16.4% (p = 0.09). Length of stay on intensive care unit (1.9 ± 1.7 vs. 2.0 ± 2.9, p = 0.88) and NYHA-class at 30 days (NYHA I/II 80.8% vs. 67.3%, p = 0.56) were not different. Conclusion: The use of SA in TA-AVI is safe. In addition to the growing experience with TA-AVI and its peri-procedural management, the introduction of SA improved outcomes after TA-AVI, with lower mortality, renal- and pulmonary complications. The use of SA possibly leads to a reduction of inflammatory response.